Content analysis of agricultural training advertisements in Nigerian newspapers - A. Oloruntoba (International Journal of Agricultural Research, Innovation and Technology, 2013)
It is obvious that the use of newspapers is one of the ways through which literate farmers could access agriculture-related information and are acquainted with innovations in agriculture. This study investigated the content of agricultural training advertisements in three Nigerian newspapers: The Guardian, Nigerian Tribune and Daily Times. Using multistage sampling techniques, 240 editions of these newspapers containing 609 advertisements for five years (2001–2005) were selected. In terms of agricultural subsectoral coverage, 30.3% were on veterinary services while forestry services recorded the least advertisement (4.0 %). The Nigerian Tribune newspaper has the highest coverage of agricultural training advertisements 40.7% compared to the 34.7% and 12.2% for Daily Times and Guardian newspapers, respectively. The result also showed that majority of agricultural training advertisements (81.10%) were placed on the non-prominent pages of the selected newspapers. Chi-Square analysis of association between the categories of agricultural training advertisements in the focal newspapers showed that there is significant relationship in the rate at which the sampled newspapers advertise different category of agricultural training advertisements in the newspapers (p<0.05). Chi square analysis also indicated that there is significant association between the placements of agricultural training advertisements and type of newspapers (p<0.05). This implies that advertisement placement on prominent pages of newspapers is determined by the policy of print media organization which also varies with cost of advertisement. It is therefore recommended that agricultural news items should be given more prominence as a panacea for increased information source to new entrants, especially the literate farmers to encourage farming.